Elaboración de salchicha escaldada “FISH EMBUTIDOS” - Caiza Gómez, Liz Mercedes (2017)
The research aims to produce sauteed sausage type frankfurt based on rainbow trout meat (Oncorhynchus mykiss) fortified with flours of quinua (Chenopodium quinoa will) bean (Vicia faba) or soybean (Glycine max) since they are raw materials that Contain great nutritional properties, proteins, c arbohydrates, fiber, vitamins, among others. In addition with this research is intended to take advantage of high nutritional content, with three concentrations and two types of preservatives (potassium sorbate and sodium nitrite) was performed as follows; Washing and disinfection of equipment, reception of raw material, filleting, weighed, chopped, ground, cut (2 ° C for 3 minutes), sausage, strained, blanched (75-80 ° C for 15 minutes), cooled (H2O At 4 ° C), packed, stored (2-4 ° C). It was submitted to organoleptic evaluation, evaluating the color, odor, flavor, texture and acceptability proving that the best treatment was t3 (bean flour 5% and potassium sorbate 0.1%). Analysis of results obtained from nutritional value are: energy 3%, calories from fat 2%, fat 5%, saturated fatty acids 8%, cholesterol 7%, sodium 4%, carbohydrates 0%, fiber 0%, protein 10%, In terms of physical and chemical characteristics, is as follows: moisture 72%, protein 13.8%, fiber 0%, total carbohydrates 0%, energy 8 KJ / 100g and 5 Kcal / 100g, fat 10.16% Ash 4.35%. In addition, it was determined, e.g. Coli, staphilococcus aureus, salmonella, which are within the limits allowed in the established standards, indicating that the product does not generate any type of danger to the health of consumers. The value of 1 kg of sausage has a retail price of $ 7.67 cts, in units of 200g sausage has a cost of 1.53 ctvs.